2020
DOI: 10.4102/sajems.v23i1.2936
|View full text |Cite
|
Sign up to set email alerts
|

Identifying regional trade potential between selected countries in the African tripartite free trade area

Abstract: Background: One of the most compelling arguments for regional trade and integration in Africa is that the African market is the most fragmented in the world, with only 16% of trade being within the continent. Furthermore, with 14 regional economic communities (RECs), the scale of integrated trading compared to the magnitude of trade is cause for concern. Africa could soon witness an important milestone on its path towards increased regional trade and improved integration with the implementation of the Triparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In the context of the Regional Trade Agreements (RTAs), there have been extensive studies [41][42][43]. Since the independence of African countries, many RTAs have organized to accelerate the sustainable development of regional economic interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of the Regional Trade Agreements (RTAs), there have been extensive studies [41][42][43]. Since the independence of African countries, many RTAs have organized to accelerate the sustainable development of regional economic interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Importer-product-exporter data on matched, untapped trade opportunities between selected TFTA countries from Ferreira and Steenkamp (2020), were employed in this study to translate the potential trade values of these untapped trade opportunities into GTAP model shocks, a unique and somewhat unconventional approach in the implementation of this model. This was done to determine what the increase in trade efficiency (reduction in trade divisions) must be, in addition to the elimination of tariffs, to produce the estimated potential increase in trade for each importer-productexporter combination.…”
Section: Methodsmentioning
confidence: 99%
“…The success of increased regional trade requires action from both the demand and the supply sides. Ferreira and Steenkamp (2020) investigated trade opportunities in the Tripartite Free Trade Area (TFTA), which aims to enhance connectivity and production linkages between EAC (East African Community), https://www.jefjournal.org.za Open Access SADC (Southern African Development Community) and COMESA (Common Market for Eastern and Southern Africa) member countries. They found that nearly 70% of trade opportunities among TFTA countries are unrealised, showing that countries outside the region are supplying the import demand for products that could have been sourced from within the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a focus on SSA, Ferreira and Steenkamp (2020) identified an array of potential intra-regional trade opportunities that would occur, with improved integration of trading relationships across the 26 member countries in the Tripartite Free Trade Agreement (FTA). The authors concluded that the level of unnecessary costs, associated with international trade in the region, must be eliminated.…”
Section: Literature Reviewmentioning
confidence: 99%